What do we know about tocolytic effectiveness and how do we use this information in guidelines? A comparison of evidence grading. Issue 13 (10th September 2013) - Roos, C; Borowiack, E; Kowalska, M; Zapalska, A; Mol, BW; Mignini, L; Meads, C; Walczak, J; Khan, KS; ,
Abstract : Background: Evidence summaries of tocolytic effectiveness assign quality levels based on a single dimension: the study design. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system takes into account several domains, including limitations of the study design and ranking the importance of outcomes. Objectives: The aim of the study was to compare the quality of evidence according to GRADE with the quality as described by existing guidelines. Search strategy: A practitioner survey to rank the importance of outcomes and a systematic review were conducted. For the systematic review, we searched Medline, Embase, and DARE databases from inception to December 2010 using the terms 'tocolytics' and 'threatened preterm labour', without any language restrictions. Selection criteria: Inclusion criteria for the review were randomised controlled trials comparing tocolytics with either placebo or betamimetics. Data collection and analysis: The review and survey teams worked independently. Evidence ratings according to GRADE were performed. Main results: The majority of the survey respondents thought that it was important to use tocolytics to buy the time needed for steroids to promote fetal lung maturation and to allow in utero transfer. Nearly 80% of 'high' ratings in guidelines were downgraded as a result of deficiencies identified by GRADE. Authors' conclusions: We propose a move away from the use of evidence rating systems reliant solely on study design, as they have a propensity towards strong recommendations when the underlying evidence is weak.